Black Soldier Fly Prepupae, Pupae, and Imago (Hermetia Illucens) Grew in Mixed Containing Fermented Coconut Pulp (FCP) and Fermented Rumen Contents (FRC) - Akbar Aditya Trihendarsa; Nurul Isnaini; Faizal Andri; Hanief Eko Sulistyo; Sri Wahjuningsih; Achadiah Rachmawati; Heni Setyo Prayogi (Journal of Agriprecision & Social Impact, 2026)
The increasing generation of organic waste has highlighted the need for sustainable bioconversion technologies, including the use of Black Soldier Fly (Hermetia illucens) larvae as efficient decomposers. This study evaluated the effects of fermented coconut pulp (FCP) and fermented rumen contents (FRC) as rearing substrates on the morphometric characteristics of BSF prepupae, pupae, and imago. A Completely Randomized Design (CRD) with five substrate formulations and 40 replications per treatment was applied. Morphometric parameters, including body length, body width, body weight, and adult abdominal dimensions, were analyzed using one-way ANOVA. The results indicated that different substrate formulations did not significantly affect any morphometric parameter (P > 0.05). Nevertheless, numerical variations were observed, with the substrate containing 85% FCPand 15% FRC (T3) tending to produce greater body dimensions, while the substrate containing 80% FCPand 20% FRC (T4) showed the greatest abdominal width. Overall, fermented coconut pulp, either alone or combined with fermented rumen contents, provided comparable nutritional conditions that supported normal BSF growth and development. These findings suggest that both organic waste materials can serve as promising alternative substrates for sustainable BSF cultivation and organic waste bioconversion.